Low-Grade Systemic Inflammation Interferes with Anabolic and Catabolic Characteristics of the Aged Human Skeletal Muscle. (7th December 2021) - Draganidis, Dimitrios; Jamurtas, Athanasios Z.; Chondrogianni, Niki; Mastorakos, George; Jung, Tobias; Grune, Tilman; Papadopoulos, Constantinos; Papanikolaou, Konstantinos; Papassotiriou, Ioannis; Papaevgeniou, Nikoletta; Poulios, Athanasios; Batrakoulis, Alexios; et al.
Abstract : Aging is associated with the development of chronic low-grade systemic inflammation (LGSI) characterized by increased circulating levels of proinflammatory cytokines and acute phase proteins such as C-reactive protein (CRP). Collective evidence suggests that elevated levels of inflammatory mediators such as CRP, interleukin-6 (IL-6), and tumor necrosis factor α (TNF- α ) are correlated with deteriorated skeletal muscle mass and function, though the molecular footprint of this observation in the aged human skeletal muscle remains obscure. Based on animal models showing impaired protein synthesis and enhanced degradation in response to LGSI, we compared here the response of proteolysis- and protein synthesis-related signaling proteins as well as the satellite cell and amino acid transporter protein content between healthy older adults with increased versus physiological blood hs-CRP levels in the fasted (basal) state and after an anabolic stimulus comprised of acute resistance exercise (RE) and protein feeding. Our main findings indicate that older adults with increased hs-CRP levels demonstrate (i) increased proteasome activity, accompanied by increased protein carbonylation and IKK α / β phosphorylation; (ii) reduced Pax7 + satellite cells; (iii) increased insulin resistance, at the basal state; and (iv) impaired S6 ribosomal protein phosphorylation accompanied by hyperinsulinemia following an acute RE bout combined with protein ingestion. Collectively, these data provide support to the concept that age-related chronic LGSI may upregulate proteasome activity via induction of the NF- κ B signaling and protein oxidation and impair the insulin-dependent anabolic potential of human skeletal muscle.